2018
DOI: 10.1016/j.antiviral.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant VSV-vectored MERS-CoV vaccine induces neutralizing antibody and T cell responses in rhesus monkeys after single dose immunization

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) has been a highly threatening zoonotic pathogen since its outbreak in 2012. Similar to SARS-CoV, MERS-CoV belongs to the coronavirus family and can induce severe respiratory symptoms in humans, with an average case fatality rate of 35% according to the World Health Organization. Spike (S) protein of MERS-CoV is immunogenic and can induce neutralizing antibodies, thus is a potential major target for vaccine development. Here we constructed a chimeric virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 40 publications
2
76
0
Order By: Relevance
“…In an analogous manner, VSVΔG was later used to create a MERS-CoV vaccine by expressing the MERS-CoV spike protein (S), and VSVΔG-MERS displayed immunogenicity in rhesus monkeys. 118 To date, no human clinical trials have been reported for VSV-based CoV vaccines and the WHO roadmap for MERS-CoV research and product development does not currently include rVSV-vectored vaccines in the port-folio of vectored vaccines. 119 Zika virus rVSV vectors have also been employed in designing vaccine candidates against Zika virus (ZIKV), a flavivirus closely related to Dengue, West-Nile, Japanese encephalitis and Yellow Fever viruses, which has been associated with severe neurological disorders such as microcephaly in newborns and Guillan-Barré Syndrome.…”
Section: Mers-and Sars-coronavirusesmentioning
confidence: 99%
“…In an analogous manner, VSVΔG was later used to create a MERS-CoV vaccine by expressing the MERS-CoV spike protein (S), and VSVΔG-MERS displayed immunogenicity in rhesus monkeys. 118 To date, no human clinical trials have been reported for VSV-based CoV vaccines and the WHO roadmap for MERS-CoV research and product development does not currently include rVSV-vectored vaccines in the port-folio of vectored vaccines. 119 Zika virus rVSV vectors have also been employed in designing vaccine candidates against Zika virus (ZIKV), a flavivirus closely related to Dengue, West-Nile, Japanese encephalitis and Yellow Fever viruses, which has been associated with severe neurological disorders such as microcephaly in newborns and Guillan-Barré Syndrome.…”
Section: Mers-and Sars-coronavirusesmentioning
confidence: 99%
“…We have recently extensively reviewed candidate MERS-CoV therapies and vaccines (Rabaan et al, 2017). Table 2 shows a summary of current and proposed therapies and vaccines, including targets, advantages and disadvantages, updated to include some potential agents that have emerged since the publication of our review (Alharbi et al, 2017;Jung et al, 2018;Langenmayer et al, 2018;Li et al, 2018;Liu et al, 2018;Niu et al, 2018;Rabaan et al, 2017;Sun et al, 2017). Development of a targeted anti-MERS-CoV therapy and availability of effective vaccines would require coordinated efforts to carry out properly controlled and organized clinical trials.…”
Section: Current and Potential Treatmentsmentioning
confidence: 99%
“…T cell and neutralizing antibody responses (Liu et al, 2018) Chimpanzee adenovirus (ChAdOx1) expressing full-length S…”
Section: In Vitromentioning
confidence: 99%
See 2 more Smart Citations